2020
DOI: 10.3390/nano10101953
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Agglomerate Intracellularly Depending on the Stabilizing Agent: Implications for Nanomedicine Efficacy

Abstract: Engineered nanoparticles are utilized as drug delivery carriers in modern medicine due to their high surface area and tailorable surface functionality. After in vivo administration, nanoparticles distribute and interact with biomolecules, such as polar proteins in serum, lipid membranes in cells, and high ionic conditions during digestion. Electrostatic forces and steric hindrances in a nanoparticle population are disturbed and particles agglomerate in biological fluids. Little is known about the stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…1 , silver content increased > 7 and > 5 times the control level in livers treated with non-coated and coated AgNPs, respectively. The results related to AgNPs penetration into hepatocytes are in agreement with other studies in vivo and in vitro 70 72 . This cellular internalization has been also reported for other metal/chitosan/curcumin nano systems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1 , silver content increased > 7 and > 5 times the control level in livers treated with non-coated and coated AgNPs, respectively. The results related to AgNPs penetration into hepatocytes are in agreement with other studies in vivo and in vitro 70 72 . This cellular internalization has been also reported for other metal/chitosan/curcumin nano systems.…”
Section: Discussionsupporting
confidence: 92%
“…in the cytoplasm, curcumin molecules will be released from the biodegradable chitosan coat and interacts with the intracellular salty conditions. Alternatively, nanoparticles remain trapped in lysosomes and endosomes 75 , where they are exposed to high ionic conditions during digestion 72 . These lysosomal digestive conditions release curcumin from chitosan coat into the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter advantage, Biswas et al [44] synthesized valsartan loaded mesoporous silica nanoparticles which showed to be capable of improving the oral bioavailability of the drug. Furthermore, a negative surface charge is associated with a rapid removal of NPs from the blood compared to the existence of a neutral charge [45].…”
Section: Characterization Methodsmentioning
confidence: 99%
“…The modification of the surface of nanoparticles is of great relevance, since, in addition to decreasing the toxicity of the initial stabilizing agents and AgNPs, it also prevents their aggregation and improves the ability to target specific cells, namely cancer cells [45]. Accordingly with Gali-Muhtasib et al [5], an efficient anticancer nanocarrier must meet some requirements: (i) affinity for the anticancer drug, allowing its conjugation; (ii) exclusive release of the drug at the target site, thus presenting specificity for the tumor; (iii) the nanoparticle-anticancer drug complex must be stable in the serum; and (iv) the nanoparticles must be degraded in a way that is safe for the living organism.…”
Section: Surface Modificationsmentioning
confidence: 99%
“…The mean particle size of Rhy-SLNs was found to be 62.06 ± 1.62 nm with a polymer dispersity index of 0.25 ± 0.01. It has been reported that the surface charge of nanoparticles could affect the stability of the nanoparticle [ 39 ]. The results in this study demonstrated that the zeta potential value of Rhy-SLNs was obtained as −6.53 ± 0.04 mV, which might prevent nanoparticle aggregation and keep their stability.…”
Section: Discussionmentioning
confidence: 99%